A connected metropolis : Los Angeles elites and the making of a modern city, 1890-1965 - Johnson, Maxwell, 1988- (University of Nebraska Press, 2023)
"A Connected Metropolis describes Los Angeles' rise in the early twentieth century as catalyzed by a series of upper-class debates about the city's connections to the outside world"--